Analysis of factors associated with continued cooling of core temperature after prolonged cold-water swimming - Drigny, J.; Hingrand, C.; Moysan, P.; Collet, T.; Mauvieux, B. (International Journal of Sports Physiology and Performance, 2023)
To assess the factors associated with continued cooling duration of core temperature (T° core) after prolonged outdoor cold water swimming. Methods: We designed a cohort study among swimmers participating in an outdoor cold-water swim during qualifying for the English Channel Swim. The day before the event, the participants completed a demographic questionnaire, and body composition was measured using bioelectrical impedance analysis (mBCA 525, Seca). The swimming event consisted of laps over a 1000-m course, for up to 6 hours, in water at 12.5 to 13 °C. T° core was measured using an ingestible temperature sensor (e-Celsius, BodyCap) during and up to 1 hour after the swim. Results: A total of 14 participants (38 [11] y; N = 14, n = 11 males, n = 8 in swimming costume and n = 6 in wetsuit) were included. Before swimming, T° core was 37.54 (0.39) °C. The participants swam for an average of 194.00 (101.94) minutes, and mean T° core when exiting the water was 35.21 (1.30) °C. The duration of continued cooling was 25 (17) minutes with a minimum T° core of 34.66 (1.26) °C. Higher body mass index (r = .595, P = .032) and fat mass (r = .655, P = .015) were associated with longer continued cooling, independent of wetsuit wear. Also, the rate of T° core drop during swimming (-1.22 [1.27] °C/h) was negatively correla ed with the rate of T° core gain after swimming (+1.65 [1.23] °C/h, r = -.682, P = .007). Conclusion: Increased body mass index and fat mass were associated with T° core continued cooling duration after prolonged outdoor cold-water swimming at 12.5 to 13 °C. The rate of T° core drop during swimming was negatively correlated with the rate of rewarming.